2022
DOI: 10.1177/20552076221116772
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perception of artificial intelligence in healthcare: A cross-sectional survey among patients

Abstract: Objective The attitudes about the usage of artificial intelligence in healthcare are controversial. Unlike the perception of healthcare professionals, the attitudes of patients and their companions have been of less interest so far. In this study, we aimed to investigate the perception of artificial intelligence in healthcare among this highly relevant group along with the influence of digital affinity and sociodemographic factors. Methods We conducted a cross-sectional study using a paper-based questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 76 publications
5
44
0
Order By: Relevance
“…Reports showed that patients are more excited about innovative technologies in healthcare than physicians because it gives them greater autonomy in their healthcare plans. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Reports showed that patients are more excited about innovative technologies in healthcare than physicians because it gives them greater autonomy in their healthcare plans. 33 …”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have reported the opposite, in which people were generally positive about utilizing AI to evaluate their radiology reports. A potential reason for this is the difference in educational levels and technical affinity among the population [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have reported the opposite, in which people were generally positive about utilizing AI to evaluate their radiology reports. A potential reason for this is the difference in educational levels and technical affinity among the population [ 15 , 16 ]. With an average score of 3.52 for the first domain (distrust and accountability), our findings indicate that participants favor human judgment over that of AI systems and that people are somewhat against the idea of AI replacing radiologists' diagnostic decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The topic of AI in health care has recently received a significant amount of attention in research, policy making, and in the general population [ 6 - 8 ]. However, the interest and attention so far have not led to the expected numbers of development and implementation activities in Europe, which have been reported by the Joint Research Centre of the European Commission [ 9 ] and in original research [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%